Genome-wide association study of cocoon-producing traits in four Henan silkworm strains revealed new candidate genes - Song, Xingya; Lyu, Yingxian; Zhang, Yuqiao; Ding, Wenjia; Huang, Yongzhen; Yang, Shang (Frontiers in Genetics, 2025)
BackgroundThe silkworm (Bombyx mori), has been farmed in China for over 5,000 years, and holds significant economic value. Recent genomic advances have deepened our understanding of silk production mechanisms, enabling the development of improved silkworm breeds. Further research is needed to identify effective molecular markers linked to silk production traits, as this will enhance genetic improvement efforts.ResultsIn the genome-wide association analysis study, we identified 40 significant single nucleotide polymorphisms (SNPs) and 28 candidate genes which were related to cocoon shell weight, cocoon width and whole cocoon weight in four silkworm strains in Henan. Through linkage imbalance block analysis, we found that the KWMTBOMO02490 (ATPase inhibitor-like protein) and KWMTBOMO12678 (OTU domain-containing protein 7B) were strongly selected. By using online databases, we found that the KWMTBOMO02490 gene was highly expressed in the posterior silk glands and may play an important role in the process of silk production.ConclusionThe candidate genes in this study may affect the production and health traits of silkworms, and may provide an important reference for silkworm breeding.